A landscape analysis of youth engagement in agripreneurship in Malawi - Kabuli, A.; Enokenwa Baa, Ojongetakah; Davis, Kristin E. (International Water Management Institute (IWMI), 2024)
This report aims to explore the multidimensional challenges and opportunities for youth in agripreneurship in Malawi for a better understanding of interventions for youth in agribusiness. It examines the enabling and disenabling environment for young agripreneurs and how best to engage youth within the agribusiness sector. The report draws on in-depth interviews, workshops, and secondary literature to highlight key issues and strategies to engage youth agripreneurs in Malawi. It also offers recommendations for actors, practitioners, and policymakers to enhance transformative interventions for youth participation in agribusiness. Suggested measures include improving access to input, market, and equipment, setting up quota systems targeting youth agripreneurs, and better coordinating youth programs between ministries and the private sectors. The report also emphasized that these strategies are not just to achieve youth inclusion in agribusiness but also for the sustainability of youth programs which contribute to building resilient societies.